Effects of Stachyose on Synbiotic Yogurt Obtained from Goat Milk with Lactobacillus acidophilus and Lactobacillus casei - Shu Guowei; Tian Mengqi; Cao Binyun; Wang Changfeng; Xin Ni (Acta Universitatis Cibiniensis. Series E: Food Technology, 2018)
Development of synbiotic yogurt having multiple health benefits has become a new trend. The purpose of this study was to obtain the optimum stachyose concentration of the goat yogurt fermented by probiotics including Lactobacillus acidophilus (LA) or Lactobacillus casei (LC) besides Streptococcus thermophilus and Lactobacillus bulgaricus by measuring pH, acidity, viable counts and the change of stachyose content. The optimal stachyose concentration of goat LA-yogurt and goat LC-yogurt were 0.4% and 0.8%. Under the above concentrations, the total bacteria number and the viable counts of LA were 2.02×109cfu/mL, 3×107cfu/mL, respectively; the total bacteria number and the viable counts of LC were 2.55×109cfu/mL, 2.53×108cfu/mL, respectively. The results indicate that stachyose can effectively improve the vitality and the viable counts of strains in goat yogurt.